2018
DOI: 10.3171/2018.1.focus17718
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of giant sphenoid wing meningiomas encasing major cerebral arteries

Abstract: OBJECTIVESphenoid wing meningiomas are a heterogeneous group of tumors with variable surgical risks and prognosis. Those that have grown to a very large size, encasing the major cerebral arteries, are associated with a high risk of stroke. In reviewing the authors’ series of giant sphenoid wing meningiomas, the goal was to evaluate how the extent of the tumor’s invasion of surrounding structures affected the ability to safely remove the tumor and restore function. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…In our series, overall complication rates were high (57%), and slightly higher (64%) in giant meningiomas. Previous studies on giant meningiomas have reported complication rates ranging from 46% to 59% [6,7,14,[17][18][19], which is in line with our results. However, the median age in our study was much higher than in the previous studies (Table 3).…”
Section: Postoperative Morbidity and Mortalitysupporting
confidence: 93%
“…In our series, overall complication rates were high (57%), and slightly higher (64%) in giant meningiomas. Previous studies on giant meningiomas have reported complication rates ranging from 46% to 59% [6,7,14,[17][18][19], which is in line with our results. However, the median age in our study was much higher than in the previous studies (Table 3).…”
Section: Postoperative Morbidity and Mortalitysupporting
confidence: 93%
“…Traditional open neurosurgical approaches have aimed for gross-total resection and is associated with significant morbidity, mostly related to traction of the brain and surgical manipulation, 23 and increases the risk of new-onset cranial nerve palsy, stroke, and mortality. 15 The open approach may inadequately address the primary symptoms of proptosis, decreased visual acuity, and pain. Thus a move to subtotal tumor resection has evolved due to the benign nature of the disease and the risk of damage to underlying vital neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that total resection via an open approach was only achieved in a minority of cases and was associated with a higher recurrence rate. 15 Therefore, the paradigm of menin-gioma surgical resection has evolved with time due to the understanding of the biology of the tumor. Although benign, they are locally invasive into surrounding bone and dura.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite vessel sacrifice and revascularization, gross total resection was only achieved in 63% [5]. In Champagne`s study, complete resection occurred in 2 out of 12 cases (Simpson grades 2 and 3) [7].…”
Section: Discussionmentioning
confidence: 99%